The monuments of the 44-day war in the everyday life of RA border settlements - Angelush, Lusine (History and Culture, 2025)
Memory plays a very important role in ethnopolitical conflicts, since public perceptions and ideas about the conflict, explanations of the justice of the struggle for the protection or liberation of one’s homeland are built on the basis of historical and cultural memory. Monumental landscapes are powerful physical manifestations of cultural memory, acting as carriers of historical narratives, expressing social values ​​and ideas about building the future.But defeat in war, territorial losses and an uncertain future may challenge dominant narratives of cultural memory, which may manifest itself in the emergence of new practices of memorialization and commemoration. These processes are particularly expressed in border settlements.This article examines the issues of rethinking cultural memory and commemoration practices in Armenian border settlements using the example of monuments from the Second Artsakh War.The article analyzes the histories of heroization and sanctification that shape cultural memory, as well as the processes of their reproduction, modification and contestation in the everyday life of society through monuments.In this context, we considered the actors in the formation of the monumental landscape, the place of installation of monuments and the role of these structures in the daily life of border settlements.The problem is discussed within the framework of sociological, anthropological and psychological theories studying the problems of individual and collective memory, ethnic and national identity and everyday life.Within the framework of the topic, research was conducted in regional centers and border settlements of Syunik, Vayotsdzor, Gegharkunik and Tavush districts of the RA, bordering Azerbaijan, using the methods of in-depth and expert interviews, observation and content analysis of Internet materials.
Keywords: war; monument; everyday life; border settlement; commemorative practices; collective participation; identity